Treskibede bulvægshuse og deres vestdanske udbredelse.: Om regionalitet og monumentalitet i ældre bronzealder periode II-III - Poulsen, Martin Egelund (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
During the Nordic Bronze Age Period II and early Period III, 1500–1200 BC, South Scandinavia experienced an increase in the construction of barrows and longhouses. Their number, dimensions and the resources involved in their construction had a dramatic effect on the landscape. On the sandy plains of western, central and southern Jutland, longhouses were particularly large, robust structures. Their walls were constructed using the bole-wall technique that involved sturdy vertical posts and horisontal planks in between – a building tradition that demanded a large quantity of oak timber. On the young moraine landscapes of eastern Jutland and the Danish Isles, houses were built using a more ephemeral wall construction tradition, that often leaves little or no archaeological traces. But what did this regional variation reflect? Why are the large timber- consuming longhouses common in the old glacial landscapes of western Denmark, while they are missing in the central and eastern parts of South Scandinavia? This can hardly be explained simply as a result of resource availability. Pollen analyses from barrows, bogs and lakes in the western parts of Jutland have clearly shown evidence for a more open grass and heath landscape, whereas the heavy moraine soils of eastern Jutland and the eastern Danish Islands seemed to have been much more forested. One could ask if house construction in the western parts of Denmark was actually dependent on timber resources from central and eastern South Scandinavia. The bole-walled longhouses are particularly characteristic to the southern part of Jutland during the Early Bronze Age and their distribution corresponds to that of the largest Early Bronze Age barrows with their iron pans and rich burials. There seems to be an intentional act of conspicuous consumption in the construction of both monumental longhouses and barrows in the south-western part of Denmark during the Early Bronze Age.